Why we assess students and how : the competing measures of student performance - McLean, James E.; Lockwood, Robert E. (United States : Thousands Oaks, Calif. : Corwin Press, 1996)
The crucial role assessments play in education is addressed in this book. The authors describe the purposes and types of assessment and discuss how assessment can best be implemented to address the concerns of parents, teachers, school administrators and the public. Detailed descriptions of norm-referenced tests, criterion-referenced tests and alternative assessment strategies are provided together with advice on their application. Issues in reducing bias and dealing with special populations are also discussed.
Keywords: Educational tests and measurements -- United States; a Academic achievement -- Evaluation -- United States